A Work study on Rockbuilt Steel and Metal Industrial Corporation - Abrena, Jasmin T. (College of Engineering, 1998)
Rockbuilt Steel and Metal Industrial Corporation is a company involved in production of steel and metal products. It is a part of a bigger company that is in charge of distributing items that they manufacture. The plant currently produces school and office equipments such as filing cabinets, safe, school lockers, and many other products in different sizes. The products of the said company basically undergo the same processes-cutting, punching, bending, assembly, painting, finishing. Having more than 15 products, the group decided to focus on the production of lateral cabinets. Careful observation and analysis presented several problem areas which are listed below : -Inability of Raw Materials - Raw materials coming from the suppliers come in late most of the time, thus, causing delays in the start of production. Inefficient Lay-out - Making use of a large portion at each department area as temporary storage inhibits the smooth flow of operations. Having no permanent storage of raw materials, the plant could not hold materials for future use, thus having to wait for supply replenishment everytime. - Lack of Well Defined Systems and Procedures in the Production Process - Poor implementation and lack of written sets of rules and regulation results to the employees being unacquainted to the actual do's and dont's of production. Lack of Maintenance Policy - Frequent breakdown of machines occur and immediate repair is not always available. The plant also lacks preventive policy regarding maintenance. Upon deliberation of these problem areas, the group came up with recommendations on having written sets of rules and regulations, a few revisions and improvement on the lay-out of the plant, and finally setting well-defined systems and procedures and guides on how to set time standards.